Efektivitas Kebijakan Harga Pangan terhadap Ketahanan Pangan - Nyak Ilham; Hermanto Siregar; D. S. Priyarsono (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2006)
EnglishThe implementation of price support policy has been facing pro and contra among the stakeholders. The experience of many developing countries in reducing their domestic support to farmers has been increasing the number of poverty incidence and threatened food security in the country. On the other side, developed countries still implement their huge domestic support to their agricultural industries. The objective of this study is to analyze the effectiveness of food price support policy to national food security; this result can be considered by the government in accelerating agriculture revitalization. This study used secondary data (time series) and analyzed using ECM. Some findings of the study show that food availability at national level could not guarantee the accessibility of food at household level. To make the price support policy effective, the price should be accomplished by other policies, especially government policy in providing rural infrastructure, increasing farmer’s income and increasing good management control in financial aspects, specifically government expenditures related to food programs.IndonesianPenerapan kebijakan harga pangan menghadapi pro dan kontra. Pengalaman negara berkembang yang mengurangi bantuan terhadap petani menyebabkan tingkat kemiskinan tidak membaik dan mengancam ketahanan pangan. Di sisi lain, negara-negara maju masih cukup besar memberi dukungan pada industri pertaniannya. Penelitian ini bertujuan menganalisis efektivitas kebijakan harga pangan yang dilakukan pemerintah terhadap ketahanan pangan nasional sehingga dapat dijadikan pertimbangan untuk merevitalisasi pertanian. Data yang digunakan merupakan data sekunder runut waktu dan dianalisis dengan model Error Correction Model (ECM). Hasil analisis menunjukkan bahwa ketersediaan pangan di tingkat nasional terbukti tidak menjamin akses pangan di tingkat rumah tangga. Untuk mengefektifkan kebijakan harga pangan perlu didukung oleh kebijakan lain, terutama kebijakan penyediaan infrastruktur, peningkatan pendapatan masyarakat, dan membenahi kebocoran-kebocoran dana yang berkaitan dengan program pangan.